PENGARUH LITERASI, INKLUSI KEUANGAN DAN PERKEMBANGAN FINANCIAL TECHNOLOGY TERHADAP MINAT MAHASISWA BERINVESTASI DI PASAR MODAL (STUDI EMPIRIS PADA MAHASISWAFAKULTASEKONOMI DAN BISNIS UNIVERSITAS MUHAMMADIYAH METRO) - Yuni Wulan Sari (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
This research aims to analyze the Effect of Financial Literacy (1), Financial Inclusion(2), and Financial Technology Development (3) Towards Student Interest in the Economics and Business Faculty, Universitas Muhammadiyah Metro when Investing in the Capital Market. This study uses a quantitative approach. The population of this research is 269 respondents. The sampling technique used is the method of using probability sampling using simple proportional random sampling with the Slovin formula so, it was obtained a sample of 150 respondents. The data in this research used SPSS version 20 by testing multiple linear regression analysis. The results of this research indicate that financial literacy had a significant effect on student interest in investing while financial inclusion and financial technology development did not significantly influence student interest in investing in the capital market, as well as financial literacy, financial inclusion, and financial technology development simultaneously.